Parity nonconservation in trinucleon bound states - Kotlyar, V.; Nogga, A. (Вопросы атомной науки и техники, 2007)
Tensor and operator representations for wave function (WF) of three–nucleon bound states are discussed. It is supposed that space parity is not conserved in interaction between nucleons. The WFs of ³He and ³H are expressed in terms of 16 scalar functions, which depend on the magnitudes of the relative momenta and the angle between them. These functions are real in the case when nuclear forces do not violate time reversal symmetry. Characteristic features appropriate to WFs of deuteron and 3N nuclei in operator form (OF) are compared.